2021
DOI: 10.1021/acsomega.1c03561
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ergosterol and Vitamin D2 in Mushrooms Agaricus bisporus and Cordyceps militaris Using Ultraviolet Irradiation Directly on Dry Powder or in Ethanol Suspension

Abstract: Vitamin D deficiency is a severe worldwide health issue. Edible mushrooms are an excellent vitamin D2 source and have gained popularity worldwide as a nutritional food. The objective of this study was to investigate the conversion efficiency of ergosterol to vitamin D2 in Agaricus bisporus and Cordyceps militaris mushrooms under ultraviolet (UV) irradiation directly through dry powder or in ethanol suspension (1:20 g/mL, solid to liquid ratio). Several parameters of UV irradiation conditions such as the materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Interestingly, we observed that the contents of cordycepin, total flavonoid and β glucan were all increased in GRC fermented with Pediococcus pentosaceus SC11, compared to GRC. Recently, it is reported that vitamin D in the Cordyceps militaris exerted the antiviral activity by inhibiting SARS-CoV-2 attachment to host cells and increasing the expression of interferon beta [80,81]. Probiotics eradicate the enteric viruses [47].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed that the contents of cordycepin, total flavonoid and β glucan were all increased in GRC fermented with Pediococcus pentosaceus SC11, compared to GRC. Recently, it is reported that vitamin D in the Cordyceps militaris exerted the antiviral activity by inhibiting SARS-CoV-2 attachment to host cells and increasing the expression of interferon beta [80,81]. Probiotics eradicate the enteric viruses [47].…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, the higher levels of phytosterols extracted from A. bisporus mushrooms using HES, compared to that obtained from C. tomentosum macroalgae, in the present work, may be related with the different phytosterols contents present in these two biomasses. 20,39 However, for both biomasses, the use of HES proved to be more efficient than the solvents or methods used previously.…”
Section: ■ Introductionmentioning
confidence: 91%
“…(2021) showed that γ‐radiation could maintain the mannose content of Agaricus bisporus powder. UV increased the vitamin D 2 (VD 2 ) content and retained more antioxidant‐active compounds of dried mushroom powders (Hu et al ., 2021; Kaur et al ., 2023). Monochrome visible light is a rich, green, clean and sustainable energy source that can mediate reactions that are difficult to achieve effectively with conventional methods under mild conditions (Zhao et al ., 2021; Li et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%